SWYER-JAMES-MACLEOD SYNDROME (SJMS) WITH PULMONARY HYPERTENSION: AN UNUSUAL CASE REPORT WITH REVIEW OF LITERATURE - Mohd Imran Shamsi; Rohit Vadala; Deepak Talwar (INTERNATIONAL JOURNAL OF SCIENTIFIC RESEARCH, 2022)
Swyer-James-Macleod syndrome (SJMS) is an uncommon disorder of the lungs resulting in unilateral hyperlucent lungs and decreased bronchovascular markings. It is typically diagnosed during childhood, although occasionally some patients are diagnosed in adulthood as an incidental nding. Pulmonary hypertension complicating this syndrome is very rare which poses a diagnostic dilemma and a challenge to manage such patients. We describe this unique case report which was initially misdiagnosed as uncontrolled bronchial asthma and later turned out to be SwyerJames syndrome associated with pulmonary hypertension.